2015
DOI: 10.1007/s00248-015-0645-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Metabolic Activity of Pediocin Producer Pediococcus acidilactici UL5: Its Impact on Intestinal Microbiota and Listeria monocytogenes in a Model of the Human Terminal Ileum

Abstract: Pediococcus acidilactici UL5 is a promising probiotic candidate due to its high survival rate under gastric and duodenal conditions and to its ability to produce the antilisterial bacteriocin pediocin PA-1. Its survival, metabolic activity, and impact on Listeria monocytogenes in a continuous stirred tank reactor containing immobilized human intestinal microbiota were studied over a period of 32 days of feeding a nutrient medium simulating ileal chyme. The impact of P. acidilactici UL5 on different bacterial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Further studies are needed to confirm that E. faecium LCW 44 inhibits Listeria in the colon in the presence of intestinal microbiota. We have already observed that P. acidilactici UL5 can reduce Listeria counts by 2 log 10 cycles after 6 h in Macfarlane broth (Fernandez et al, 2013) but not in a continuous stirred tank reactor containing immobilized human intestinal microbiota (Fernandez et al, 2015). With its short generation time and high adaptability to different growth conditions, E. faecium LCW 44 is expected to compete well with colonic microbiota and to inhibit Listeria under gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to confirm that E. faecium LCW 44 inhibits Listeria in the colon in the presence of intestinal microbiota. We have already observed that P. acidilactici UL5 can reduce Listeria counts by 2 log 10 cycles after 6 h in Macfarlane broth (Fernandez et al, 2013) but not in a continuous stirred tank reactor containing immobilized human intestinal microbiota (Fernandez et al, 2015). With its short generation time and high adaptability to different growth conditions, E. faecium LCW 44 is expected to compete well with colonic microbiota and to inhibit Listeria under gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from an overnight culture of each strain using the wizard genomic DNA purification kit (Promega, Madison, WI, United States) as described by Fernandez et al (2015). The 16S ribosomal DNA was amplified by PCR (Eppendorf Mastercycler gradient, Hamburg, Germany) with 27f 5′-AGAGTTTGATCMTGGCTCAG-3′ (Gürtler and Stanisich, 1996) and 1390r 5′-GACGGGCGGTGTGTACAA-3′ (Zheng et al, 1996) primers (Invitrogen, Carlsbad, CA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Standard curve for the qPCR quantification was done using the following strains: E. coli ATCC 25922, B. adolescentis ATCC15703, B. thetaiotaomicron ATCC29741, C. leptum ATCC29065, B. coccoides ATCC29236, and E. faecalis ATCC27275. Samples were collected from the reactor and treated with propidium monoazide (Biotium, Inc., Hayward, CA, USA) prior enumeration of viable bacteria, as described in Fernandez et al (2015) . The DNA from fecal and fermentation samples were then extracted following the protocol of Ahlroos and Tynkkynen (2009) using the Wizard ® genomic DNA Purification Kit (Promega, Madison, WI, USA) with some modifications ( Fernandez et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were collected from the reactor and treated with propidium monoazide (Biotium, Inc., Hayward, CA, USA) prior enumeration of viable bacteria, as described in Fernandez et al (2015) . The DNA from fecal and fermentation samples were then extracted following the protocol of Ahlroos and Tynkkynen (2009) using the Wizard ® genomic DNA Purification Kit (Promega, Madison, WI, USA) with some modifications ( Fernandez et al, 2015 ). Real-time PCR was carried out on an ABI 7500 real-time PCR system (Applied biosystem, Streetsville, ON, Canada) with the iTaq TM Universal SYBR ® Green supermix (Biorad, Oakville, ON, Canada) in 96-well plates following method described in Fernandez et al (2015) .…”
Section: Methodsmentioning
confidence: 99%
“…The most important appeal of bacteriocins as antibacterial agents and antibiotic substitutes is their multiple advantages over other antimicrobial agents commonly used in food preservation and handling, animal production and in human and veterinary medicine. For example, bacteriocins have been shown to be: (i) safe for consumption since they are completely digested in the gastrointestinal tract ( Kheadr et al, 2010 ; Fernandez et al, 2016 ), (ii) highly potent (10 3 to 10 6 times more than several other antimicrobials including conventional antibiotics); (iii) resistant to common thermal treatments for pasteurization or even sterilization ( De Vuyst and Leroy, 2007 ; Keymanesh et al, 2009 ; Abriouel et al, 2010 ). Moreover, several bacteriocins are recognized as GRAS (generally recognized as safe) substances by the United States Food and Drug Administration (FDA) and the European legislation for pharmaceutical and food industry uses.…”
Section: Introductionmentioning
confidence: 99%